ORGANIZING E-LEARNING OF PHYSICS – EDUCATIONAL ACTIVITIES IN OUT-OF-SCHOOL HOURS (Journal of Information Technologies in Education (ITE), 2012)
Experience of organizing pedagogical experiment – an open distance course «Introduction in acoustics» is analyzed in this paper.
Keywords: cognitive activity; distance course; pedagogical experiment